Structural and dynamic studies of Zr-based metal-organic frameworks toward external stimuli - Yoskamtorn, T (2021)
Advanced studies of structures and dynamics of functional materials based on metal-organic frameworks (MOFs) showing exceptional stimuli-driven properties is of strong current interest for the design of next-generation smart materials, especially for sorption-based applications such as gas storage, energy storage, controlled drug delivery, and molecular sensing, to name but a few. State-of-the-art diffraction and spectroscopy in conjunction with theoretical calculations are one of the most powerful approaches to achieve these detailed analyses at a molecular level. This thesis aims to study mechanistic aspects of stimuli-responsive behaviours responsible for a distinctive stepwise ammonia (NH3) adsorption in the defect-rich Zr-based metal-organic frameworks (MOFs), namely UiO-67 and its isostructural UiO-bpydc, both experimentally and computationally. In Chapter 3, high-resolution neutron and synchrotron diffractions along with Rietveld refinement and density functional theory (DFT) calculations have been used to characterise the binding domains and the interactions of NH3/ND3 with defect-rich UiO-67 and UiO-bpydc containing biphenyl dicarboxylate and bipyridine dicarboxylate linkers, respectively. The results establish that the dramatic alteration of stepwise adsorption processes is closely associated with hydrogen bonding network between NH3/ND3 and the frameworks at the disordered/defective trigonal and lozenge pore windows of the materials without significant change in pore volume and unit cell parameters. Specifically, UiO-bpydc is possible to make stronger and more extensive hydrogen bonding using pyridine sites of the linker than in UiO-67. These molecular controls lead to stimulus-tailoring properties such as gate-controlled porosity by dynamic linker flipping, disorder, and structural rigidity which are further confirmed by temperature-dependence of in situ structural analyses accompanied with guest-induced rotational motions of the organic linkers studied by DFT in Chapter 4. To get deeper insights into the interesting NH3-induced stepwise adsorption, the dynamic features of the MOF-NH3 systems have been further investigated by using advanced inelastic neutron scattering (INS), quasi-elastic neutron scattering (QENS) in conjunction with theoretical calculations. Guest-induced linker stiffening reflected by the suppression of lattice motions of the host frameworks upon NH3 adsorption is achieved, which exhibits greater effect in the UiO-bpydc case. More excitingly, analysis of INS difference spectra reveals heterogeneous dynamics of the trapped NH3 depending on MOF functionality and gas loading. For the UiO-67, the well-ordered NH3 molecules primarily adsorbed at μ3-OH have more feasibility to undergo progressive interactions with the incoming NH3 molecules, signifying its more accessible porous structure for NH3 inclusion due to the lack of guest-stimulated pore blocking conversely observed in the UiO-bpydc. QENS study elucidates negligible mobility of NH3 in both MOFs at the lowest dosage, indicative of the similar localised diffusion caused by strongly bound NH3 at the μ3-OH sites of the hosts. On the other hand, the NH3 diffusivities in these frameworks become distinct at higher NH3 uptake where the stepped adsorption occurs. This observation points toward the confined NH3 molecules experiencing a diversity of either pore environments or host-guest interactions.